Sustainable Tourism Development in Jordan: Destination Attributes Effects Tourist Expenditure. A Case Study of Domestic Tourism in Aqaba Ci - ALROUSAN, Ramzi; IBRAHIM, Hussein; BADER, Malek; ABUAMOUD, Ismaiel (Journal of Environmental Management and Tourism; Vol 7 No 4 (2016): JEMT Volume VII Issue 4(16) winter 2016DO - 10.14505/jemt.v7.4(16).21, 2019)
The current study discusses the relationship between destination attributes and its influence on tourists' expenditure. The model used in this study is based on economic theory of consumer behavior to examine and explain the consumption behavior of domestic tourists visiting Aqaba city in Jordan. A total of 417 surveys were administrated to Jordanian tourists who visited Aqaba city. In order to obtain accurate and reliable, data was collected after they completed their trips. The resultsshow that destination attributes are closely linked tourists’ expenditure and proved that destination attributes had influence on tourists' expenditure.The current study provides a comprehensive picture of domestic tourism market and would be a useful reference point to Jordanian authorities and stakeholders to plan and implement policies that would encourage domestic tourism in Jordan.